Thermal ablation of mucosal defect margins reduces adenoma recurrence after colonic endoscopic mucosal resection - Keklikkıran, Çağlayan; Özdoğan, Osman Cavit (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Keklikkıran Ç, Özdoğan OC. Thermal ablation of mucosal defect margins reduces adenoma recurrence after colonic endoscopic mucosal resection. Turk J Gastroenterol 2019; 30(6): 580-1.